ANALISA KINERJA KEUANGAN TERHADAP RETURN SAHAM DENGAN INFLASI SEBAGAI VARIABEL MODERASI PADA INDUSTRI CONSUMER GOODS YANG TERDAFTAR DALAM INDEKS SAHAM SYARIAH INDONESIA (ISSI) PERIODE 2014-2018 - Eva Purnamasari; Ardiansyah Japlani (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
This research is designed to analyze the influence of financial performance, proxied by Net Profit Margin, Current Ratio, Debt to Asset Ratio, Total Asset Turnover, and Earnings per Share to stock return, with inflation factor as moderate variable. The study was conducted on sharia shares in the consumer goods sector, that listed on the Indonesia Sharia Sharia Index (ISSI) in the period 2014-2019. Method of sampling research using purposive sampling method, with quantitative data, and the sample taken is as much as twenty two consumer goods’ shares. Methods of data analysis in this study by using multiple linear regression analysis and Moderate Regression Analysis (MRA). The test results show that partially Net Profit Margin, Debt to Asset Ratio, and Total Asset Turn Over have a positive and significant impact on Sharia stock returns in consumer goods sector. While Current Asset and Earnings per Share partially have no significant effect on the return of sharia stocks in the consumer goods sector. If tested simultaneously and simultaneously, the five financial ratios have a significant effect on Sharia stock returns in the consumer goods sector. The rate of inflation in the testing of this study proved to be a moderating variable and able to strengthen the effect of financial performance on Sharia stock returns in the consumer goods sector.